2018
DOI: 10.1101/384776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide CRISPR Screens in Primary Human T Cells Reveal Key Regulators of Immune Function

Abstract: SUMMARYHuman T cells are central effectors of immunity and cancer immunotherapy. CRISPR-based functional studies in T cells could prioritize novel targets for drug development and improve the design of genetically reprogrammed cell-based therapies. However, large-scale CRISPR screens have been challenging in primary human cells. We developed a new method, sgRNA lentiviral infection with Cas9 protein electroporation (SLICE), to identify regulators of stimulation responses in primary human T cells. Genome-wide l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 73 publications
0
62
0
Order By: Relevance
“…CS therefore reflects the relative deleteriousness of LOF on cell proliferation ( Fig EV1): A lower CS value indicates more deleteriousness and vice versa. These datasets are (i) CS1 from four cell lines (Wang et al, 2015), (ii) CS2 from 450 cell lines (Meyers et al, 2017;DepMap, 2018), (iii) CS2.1 from 450 cell lines (DepMap, 2018), and (iv) CS3 from 1 primary cell line (Shifrut et al, 2018; see Dataset EV2 for cell-line information, Dataset EV3 for gene-wise CS values). All the CS values capture the essentiality of the genes which, in the case of cancer cell lines, are found to be largely independent of the role of the genes in cancerogenesis ( Fig EV1).…”
Section: Paralogous Genes Protect Against the Effect Of Gene Lof Acromentioning
confidence: 99%
See 3 more Smart Citations
“…CS therefore reflects the relative deleteriousness of LOF on cell proliferation ( Fig EV1): A lower CS value indicates more deleteriousness and vice versa. These datasets are (i) CS1 from four cell lines (Wang et al, 2015), (ii) CS2 from 450 cell lines (Meyers et al, 2017;DepMap, 2018), (iii) CS2.1 from 450 cell lines (DepMap, 2018), and (iv) CS3 from 1 primary cell line (Shifrut et al, 2018; see Dataset EV2 for cell-line information, Dataset EV3 for gene-wise CS values). All the CS values capture the essentiality of the genes which, in the case of cancer cell lines, are found to be largely independent of the role of the genes in cancerogenesis ( Fig EV1).…”
Section: Paralogous Genes Protect Against the Effect Of Gene Lof Acromentioning
confidence: 99%
“…The extent of depletion is measured as a CRISPR score (CS, see Materials and Methods). CS values across cell lines from three biologically independent datasets-CS1 (Wang et al, 2015), CS2/CS2.1 (Meyers et al, 2017;DepMap, 2018), and CS3 (Shifrut et al, 2018) are shown. Genes that are not in the paralog datasets but that were not identified as singletons in the stringent identification of singletons are denoted as "unclassified".…”
Section: Paralogous Genes Protect Against the Effect Of Gene Lof Acromentioning
confidence: 99%
See 2 more Smart Citations
“…Use of the clustered regularly interspaced short palindromic repeat (CRISPR) and CRISPR‐associated protein 9 (Cas9) system has revolutionized genome editing both in human (Shifrut et al, ) and microorganisms (Chen, Zhang, Yeo, Bae, & Ji, ; Vyas, Barrasa, & Fink, ). Briefly, the system requires two core components: a functional Cas9 protein to generate DNA double‐strand breaks (DSBs) and a single guide RNA (sgRNA) to guide the Cas9 endonuclease to any targeted locus in the chromosome with an appropriate protospacer adjacent motif (PAM).…”
Section: Introductionmentioning
confidence: 99%